Porous Zinc Anode Design for Zn-air Chemistry - Liu, Peiyuan; Ling, Xiaofei; Zhong, Cheng; Deng, Yida; Han, Xiaopeng; Hu, Wenbin (Frontiers in Chemistry, 2019)
Zinc-air battery has drawn increasing attention from the whole world owing to its large energy capacity, stable working voltage, environmentally friendship, and low price. A special porous Zn with three-dimensional (3D) network frame structure, whose multistage average pore sizes can be tuned from 300 to 8 um, is synthesized in this work. It is found that there is a competition between Zn2+ and NH4+ for their reduction on the supports. And the decrease of Zn2+ concentration and increase of NH4+ concentration can facilitate the decrease of pore size. Potential-dynamic polarization was tested with 3-electrodes cell, aiming to characterize the electrochemical activity and corrosion properties of porous Zn and commercial Zn foil electrodes. After optimization, the porous Zn prepared with the parameters of 3 M NaBr, 1 M C2H3O2NH4, and 0.01 M C4H6O4Zn shows the most negative corrosion potential of −1.45 V among all the samples, indicating the remarkable anti-corrosion property. Its discharge specific capacity is up to 812 mAh g−1. And discharge-charge test of the porous Zn shows an initial discharge platform of 1.33 V and an initial charge platform of 1.96 V, performing a small overpotential. What's more, the porous Zn exhibits a much longer cycle life than commercial Zn foil. Our work will not only shed light on the design and synthesis of other porous metal materials, but also further promote the development of Zn-based battery electrochemistry.